Can a community-based maternal care package in rural Ethiopia increase the use of health facilities for childbirth and reduce the stillbirth rate? - Atnafu H; Belete Z; Kinfu H; Tadesse M; Amin M; Ballard KD (Dove Medical Press, 2016)
Habtamu Atnafu, Zelalem Belete, Hirut Kinfu, Mebkyou Tadesse, Mohammed Amin, Karen D Ballard Hamlin Fistula Ethiopia, Addis Ababa Fistula Hospital, Addis Ababa, EthiopiaObjective: To measure the impact of a maternal health package on health facility delivery and stillbirth rates.Methods: This is a cross-sectional study in Ethiopia where a maternal package was integrated into eight health centers across three regions. The package included trained midwives with a mentoring program, transport for referral, and equipment and accommodation for the midwives. Ten health centers without the package but in the same districts as the intervention centers and eight without the package in different districts were randomly selected as the comparison groups. Women living in the catchment areas of the 26 health centers, who delivered a baby in the past 12 months, were randomly selected to complete a face-to-face survey about maternal health experiences.Results: The maternal package did not significantly affect the stillbirth or facility delivery rates. Women were positively influenced to deliver in a health facility if their husbands were involved in the decision concerning the place of birth and if they had prior maternal experience in the health center. Barriers to delivering in a health facility included distance and ability to read and write.Conclusion: Women served by health centers with a maternal health package did not have significantly fewer stillbirths and were not more likely to deliver their babies in a health facility. Husbands played an important role in influencing the decisions to deliver in a health facility. Keywords: maternal health, institutional delivery, stillbirth, predictive factors, Ethiopia, global health